Quantum State Sharing of An Arbitrary Three-qubit State Using Two Four-qubit Cluster States - Ting Zhang; Xiu-Li Tu; Xian-Ming Wang; Xin-Wei Zha (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
A scheme of quantum state sharing(QSTS) an arbitrary three-qubit state is presented using two particular four-qubit cluster state as the quantum channel. With four Bell pairs state measurements and the local unitary operation, any one of the two agents has the access to reconstruct the original if he/she collaborates with the other one. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2566